Multivariate methods for Investigating Academic Stumbling: A Case Study Faculty of Economics and Rural Development, University of Gezira State, Sudan (2017) - Ahmed Mohamed, Adel Ali; Eltahir, Mawda Salah Hassan (IJRDO - Journal of Social Science and Humanities Research, 2018)
The importance of factor analysis is to summarize many of the variables to a smaller number of variables known factors. The aim of the research to find out the academic stumble students of the Faculty of Economics and Rural Development, University of Gezira. A sample of 100 students was tested using A questionnaire form consisting of three axes applied to the area of the study. The analytical descriptive method was used and one of the methods of multiple variables (Factor Analysis) was used the Statistical Packages for Social Sciences (SPSS). The results indicate that the main weights affecting the first factor were weak motivation and desire to study and desire to work and work more than the study either affect the second factor is the disintegration of the family because of divorce or otherwise Accordingly, the third factor was affected by the weakness of the mental abilities and the difficulty in absorbing some subjects. The adoption of some faculty member’s inappropriate methods in teaching led to a gap between the needs of the student and the content of the subject. Accordingly, the research came out with the recommendations of intensifying the process of guidance in the departments and taking care of academically stumbled students.